Chagas disease: an impediment in achieving the Millennium Development Goals in Latin America - Barragán Maribel; Rodríguez-Morales Alfonso J; Tellez Ildefonso; Hidron Alicia; Von Anna; Franco-Paredes Carlos; Jones Danielle; Náquira Cesar G; Mendez Jorge (BMC, 2007)
Abstract Background Achieving sustainable economic and social growth through advances in health is crucial in Latin America within the framework of the United Nations Millennium Development Goals. Discussion Health-related Millennium Development Goals need to incorporate a multidimensional approach addressing the specific epidemiologic profile for each region of the globe. In this regard, addressing the cycle of destitution and suffering associated with infection with Trypanosoma cruzi, the causal agent of Chagas disease of American trypanosomiasis, will play a key role to enable the most impoverished populations in Latin America the opportunity to achieve their full potential. Most cases of Chagas disease occur among forgotten populations because these diseases persist exclusively in the poorest and the most marginalized communities in Latin America. Summary Addressing the cycle of destitution and suffering associated with T. cruzi infection will contribute to improve the health of the most impoverished populations in Latin America and will ultimately grant them with the opportunity to achieve their full economic potential.